Associations between Predictors of PTSD and Psychosocial Functioning in Veterans: Results from a Longitudinal Assessment Study - Pearson, R.; Mendoza, C.; Coppin, J. D.; Creech, S. K. (Depression and Anxiety, 2024)
Impairments in psychosocial functioning are common in veterans, especially in those with significant mental health symptoms. Although available treatments are aimed at alleviating these symptoms, impairments in psychosocial functioning do not appear to be fully addressed. To achieve rehabilitation and full societal participation, there is a need to identify longitudinal associations of both symptoms and functional outcomes which can be targeted in treatment. United States veterans (N=491) of the Iraq and Afghanistan wars were recruited as part of a longitudinal assessment study which examined predictors of postdeployment adjustment. Veterans were assessed at four timepoints over the course of a two-year period. A Bayesian multivariate multilevel model was used to estimate the association of predictors of PTSD (depression, alcohol use, suicidal ideation, and sleep) on psychosocial functioning as encompassed by quality of life (Quality of Life Scale (QLS)) and disability (World Health Organization Disability Assessment Schedule (WHODAS)) scores over time. As female veterans have unique environmental exposures and functional demands, interactions between predictors and gender were included in all models. There was significant overlap between predictors of PTSD and predictors of disability across domains and quality of life. Depressive symptoms and social support emerged as the strongest predictors of psychosocial functioning. Additionally, suicidality and alcohol use emerged as predictors of quality of life, but not disability. As expected, increases in PTSD symptoms predicted increased disability and decreased quality of life. The effect of depressive symptoms on quality of life was more pronounced for male veterans, and the effect of PTSD and alcohol use on quality of life was more pronounced for female veterans. Findings highlight various treatment targets which have the potential to improve symptoms of PTSD and functional outcomes. Findings highlight an opportunity to leverage intervention and prevention efforts focused on decreasing depression and increasing social support to improve trauma symptoms and maximize rehabilitation and functional recovery in veterans.